ALASAN PEMAAF SEBAGAI DASAR MENGHAPUSKAN PERTANGGUNGJAWABAN PIDANA DALAM TINDAK PIDANA NARKOTIKA - Merry Aprillyani (Fakultas Hukum Universitas Tarumanagara, 2021)
The excuse for forgiveness is a reason that eliminates the perpetrator's guilt but his actions are still declared as an unlawful act. One of the things that can be a reason for forgiveness is if someone has a mental disorder, then he will be released from all lawsuits. However, in practice, not all narcotics criminals who are indicated to have mental disorders can apply forgiving reasons for themselves. The formulation of the problem that will be discussed in this study is how the reason for forgiveness is the basis for eliminating criminal liability in narcotics crimes? This study aims to examine and analyze the reasons for forgiveness as the basis for eliminating criminal liability in narcotics crimes. This research is a normative legal research with analytical descriptive nature and the data is collected by using literature study technique. This study uses a law approach and a case approach and uses a qualitative juridical analysis method. The results of this study are not all mental disorders can be the reason for the implementation of excuses. To ensure the defendant's mental condition, it is necessary to carry out a mental health examination by a psychiatric specialist based on Permenkes No. 77/2015. From the examination process, results will be obtained regarding the type of mental disorder of the defendant, the nature of the mental disorder of the defendant, the role/responsibility of the mental disorder of the defendant for the crime he committed, and the ability to be responsible for the defendant which is then summarized in a Psychiatric Visum et Repertum to be the main consideration for the judge. in enforcing excuses. In addition to considering the VeRP, other evidence such as witness statements will also be considered by the judge to build confidence in him.